Level of patients’ knowledge, confidence, and acceptance regarding the role of residents in a family medicine teaching clinic - Babin, Lise; Cormier, Isabelle; Champagne, Sylvie; MacIntosh, Jason; Saucier, Dany; Thibault, Véronique; Barrieau, André; Bélanger, Mathieu (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Background: Although participation of patients is essential for completing the training of medical residents, little is known about the relationships among patients’ level of knowledge about the role and responsibilities of medical residents, their confidence in residents’ abilities, and their acceptance toward receiving care from residents. The study sought to clarify if and how these three patient-resident relationship components are interrelated.Methods: This is a cross-sectional study using a self-administered questionnaire distributed in 2016 to a convenience sample of adult patients (≥ 18 years old) visiting a family medicine teaching clinic. Proportions and chi-square statistics were used to describe and compare groups, respectively.Results: Of the 471 patients who answered the questionnaire, only 28% were found to be knowledgeable about the role of family medicine residents. Between 54% and 83% of patients reported being highly confident in the ability of residents to perform five routine tasks. Of the patients surveyed, 69% agreed to see a resident during their next appointments. Patients with a high level of confidence in residents’ abilities were more likely to agree to see a resident during future appointments (p <0.0001). There was no significant association between level of knowledge and either confidence or acceptance.Conclusions: Although the majority of patients had poor knowledge about the role of residents, this was not related to their acceptance of being cared for by residents. A higher level of confidence in residents’ ability to perform certain tasks was associated with greater acceptance toward seeing a resident during future appointments.